A System Review: Effect of Robot-assisted Training on Improvement of Lower Extremities Function of Stroke Patients in Early Rehabilitation - Xuejing LI; Jiajia WU; Tao YE; Qiang TANG (康复学报)
Objective:To systematically review the effect of robot-assisted training on lower extremities function of stroke patients in the early stage of rehabilitation.Methods:We electronically searched databases including PubMed, EMbase, Clinicaltrials.gov, EBSCO, CNKI, and WanFang to collect randomized controlled trials (RCTs) about robot-assisted training for improvement of lower extremities motor and balance function of patients in early stage of stroke (duration<1 month) which published before October 2017. Two reviewers independently screened literature, extracted data and assessed the risk of bias of included studies. Meta-analysis was performed by using RevMan 5.3 software.Results:Five trials involving four Chinese literatures and one English literature were enrolled in this Meta-analysis. The results demonstrated that, compared with conventional training group, the score of Fugl-Meyer assessment (lower extremity) in robot-assisted training group was increased [SMD 0.76; 95%CI (0.46, 1.07), P<0.01], and Berg balance scale was also increased [SMD 0.62; 95%CI (0.32, 0.92), P<0.01].Conclusion:Current evidence showed that robot-assisted training could improve the lower extremities motor function and balance of patients in early stage of stroke. It still needs to be confirmed in a larger scale of controlled studies with a more homogeneous group of patients and a longer follow-up. Optimum parameters of rehabilitation robot, such as body weight support, guide force, gait speed, need to be further studied in patients in different stages of stroke.